Key Articles and Guidelines in the Management of Heart Failure: 2018 Update. (February 2019) - Jackevicius, Cynthia A.; Page, Robert L.; Buckley, Leo F.; Jennings, Douglas L.; Nappi, Jean M.; Smith, Andrew J.
Heart failure is one of the leading causes of hospitalizations in the United States, with >1 million admissions yearly and a 25% risk of readmissions within 1 month. In order to assist clinicians, we provide an update of the heart failure bibliography that was published in Pharmacotherapy in 2008, which followed the original bibliography published in 2004. A significant number of clinical trials and observational studies have been conducted since the early 1980s to guide management of heart failure patients. Major advances have occurred in the past 10 years, and our understanding of the diagnosis, prevention, and management of heart failure has evolved substantially during this time period. Specific areas of this review include heart failure risk factors, management of comorbid conditions, acute heart failure management, chronic heart failure management, advanced heart failure, device therapy, lifestyle modification, and medication and therapy management, including medication adherence. Key consensus guidelines and statements are also included. This bibliography of key heart failure papers aims to provide clinicians and their trainees with a valuable clinical reference resource and teaching tool that may be used to optimize the care of patients with heart failure.